Secularism as a Project of Free and Equal Citizenship: Reflections on the Turkish Case - Gülalp, Haldun (Frontiers in Sociology, 2022)
This article undertakes a defense of secularism, much maligned by postmodernists and multiculturalists. First, secularism as a normative political principle is conceptually distinguished from the discredited sociological theory of secularization and, second, it is treated as a project of free and equal citizenship. The conceptual discussion is complemented by an assessment of the Turkish case, falsely presented in the literature as a radical form of secularism. The article aims to show that a religious political movement, opposed to secularism, tends to be authoritarian and intolerant of diversity.